Voltage Deviations Influence on Asynchronous Characteristics of Powerful Asynchronized Turbogenerator - Kostiantyn Pokrovskyi; Andriy Muzychak (Energy Engineering and Control Systems)
The widespread applying of electrical grids with voltage classes 330 and 750 kV with powerful units of nuclear and heat power plants creates a set of problems with normal modes ensuring in the Ukrainian energy system. Due to sufficiently great transverse capacitance of such overhead lines, significant amounts of reactive power excess are possible in the system. This phenomenon manifests itself especially in the load reduction hours in the power system through the visible voltage levels deviation at the energy-generating nodes in an upward direction. The application of asynchronized turbogenerators with the ability to work in asynchronous mode could solve the problem of reactive power excesses in the energy-generating nodes during load reduction hours in the power system due to their possibility of deep reactive power consumption. The paper presents the calculated results of the asynchronous modes coordinates for an asynchronized turbogenerator with a capacity 1000 MW based on the parameters of the equivalent circuit, taking into account possible generator stator voltage deviations within ±10%. The influence of voltage deviations on the asynchronous modes coordinates is shown. Due to the obtained characteristics, it is possible to perform engineering estimations of the possible asynchronous mode applying for the asynchronized generator under conditions of nuclear and thermal power plants and taking into account possible voltage deviations.